PENGARUH PEMBELAJARAN KOOPERATIF (COOPERATIVE LEARNING) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 LATAMBAGA - Irmayani Irmayani; Muhammad Asra; Suhardin Suhardin (Jurnal Teknologi Pendidikan Madrasah, 2023)
This study uses quantitative descriptive analysis with a sample of 210 respondents, from the Likert scale used the average respondent answered 3.56 points, it can be seen that students' perceptions of online learning some time ago were effective. This study discusses the effect of cooperative learning on student learning outcomes in Islamic religious education subjects at SMA Negeri 1 Latambaga. The purpose of this study was to determine the extent to which the effect of cooperative learning on student learning outcomes using the Jigsaw method. The type of research used by researchers is a quantitative approach. The variables of this study are cooperative learning (X) and learning outcomes (Y). The number of samples used by researchers in this study were 155 students. The research instrument used in research is using cooperative learning questionnaires on learning outcomes. Based on the results of the research analysis that has been carried out, it was found that there was an influence of cooperative learning on learning outcomes at SMA Negeri 1 Latambaga. This can be seen from the data that has been processed by SPSS in class XI, namely 7,419 with a significant value of 000 <0.05, so the processing results prove that there is an effect of cooperative learning on student learning outcomes.